Prevalence of Anemia in Pediatric IBD Patients and Impact on Disease Severity: Results of the Pediatric IBD-Registry CEDATA-GPGE®. (5th December 2017) - Laffolie, Jan de; Laass, Martin W.; Scholz, Dietmar; Zimmer, Klaus-Peter; Buderus, Stephan; ,
Abstract : Aim . To determine the prevalence of anemia and its association with disease severity in children and adolescents with IBD. Methods . CEDATA-GPGE is a registry for pediatric patients with IBD in Germany and Austria from 90 specialized centers. As markers of disease severity, analysis included patient self-assessment on a Likert scale (1–5; 1 = very good) and physicians' general assessment (0 = no activity to 4 = severe disease) and the disease indices. Anemia was defined as hemoglobin concentration below the 3rd percentile. Results . Prevalence of anemia was 65.2% in CD and 60.2% in UC. Anemic CD and UC patients showed significantly worse self-assessment than patients without anemia (average ± standard deviation; CD: 3.0 ± 0.9 versus 2.5 ± 0.9, p < 0.0001 ; UC: 2.9 ± 0.9 versus 2.3 ± 0.9, p < 0.0001 ). Accordingly, physicians' general assessment (PGA) was significantly worse in anemic than in nonanemic patients in CD (p < 0.0001 ) and UC (p < 0.0001 ). PCDAI in anemic CD, p < 0.0001, and PUCAI in anemic UC patients, p < 0.0001, were significantly higher than in nonanemic patients. 40.0% of anemic CD and 47.8% of anemic UC patients received iron during follow-up. Conclusion . Almost 2/3 of pediatric IBD patients are anemic. Patients' self-assessment and disease severity as determined by PGA and activity indices are worse in anemic patients. Contrastingly, only a minority received iron therapy.